PKM Pelatihan Penulisan Karya Ilmiah Bagi Pelajar SMK Di Kabupaten Simalungun Dan Kota Pematangsiantar - Wanto, Anjar; Lubis, Muhammad Ridwan; Parlina, Iin (Jurnal TUNAS, 2019)
This training aims to foster and increase interest in writing, especially writing scientific papers for vocational students in Simalungun Regency and Pematangsiantar City. This dedication is carried out in 2 different Vocational Schools which are Partners of the dedication team, Partner 1 is the National Children's Vocational School located in Simalungun district and an exemplary Private Vocational School located in Pematangsiantar City. The activity was held for 4 days during July 2019, at the National Private Vocational School. The activity was carried out on Saturday and Sunday 6-7 July 2019, starting at 08.00-17.00 WIB with 52 students participating, while the Exemplary Private Vocational School was held on the 13th -14 July 2019 at the same time, with 25 students. The targets of this activity are vocational students in Simalungun District (SMK Anak Bangsa) and Pematangsiantar City (Exemplary SMK). The reason for the selection of service locations is because of the lack of student interest in these schools in terms of writing scientific papers, as well as the lack of scientific papers produced. This activity uses the method of presentation / lecture, discussion, question and answer, and practice / practice. The results of this community service activity show that out of 52 student participants in the Vocational School Private Nation, 25 students were able to answer the questions (Post Test) correctly as many as 10 questions (48%) where previously only able to answer the questions (Pre Test) correctly 9 questions as many as 8 participants (15%). While from 25 student participants in Exemplary Private Vocational Schools, 12 students were able to answer questions (Post Test) correctly as many as 10 questions (48%) where previously only able to answer questions (Pre Test) correctly 9 questions as many as 2 participants (8%).